PRMT1 Promoted HCC Growth and Metastasis In Vitro and In Vivo via Activating the STAT3 Signalling Pathway - Xiu-Ping Zhang; Ya-Bo Jiang; Cheng-Qian Zhong; Ning Ma; Er-Bin Zhang; Fan Zhang; Jing-Jing Li; Yue-Zhen Deng; Kang Wang; Dong Xie; Shu-Qun Cheng (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Although it has been widely accepted that protein arginine methyltransferase 1 (PRMT1) is a cancer-promoting gene in various cancers, the mechanism of PRMT1 in hepatocellular carcinoma (HCC) requires more exploration. This study aimed to investigate the role of PRMT1 in HCC growth and metastasis. Methods: We compared PRMT1 expression and clinicopathological characteristics using paired HCC and adjacent noncancerous liver tissues from 210 patients and immunohistochemistry analyses. Cell proliferation, colony formation and migration were determined in HCC cell lines with PRMT1 overexpression or downregulation through MTT, crystal violet and Boyden chamber assays. Tumour growth was monitored in a xenograft model, and intrahepatic metastasis models were established. Results: PRMT1 expression was greatly increased in clinical HCC samples and strongly associated with poor prognosis and recurrence; PRMT1 expression was also positively correlated with microvascular invasion (P = 0.024), tumour differentiation (P = 0.014), tumour size (P = 0.002), and portal vein tumour thrombus (PVTT) (P = 0.028). Cell proliferation, colony formation and migration in vitro were enhanced by PRMT1 upregulation and decreased by PRMT1 downregulation in HCC cell lines. Moreover, low PRMT1 expression resulted in slow tumour growth and decreased tumour weight in vivo, as well as tumour metastasis. These phenotypes were associated with STAT3 signalling pathway activation. Cryptotanshinone, a STAT3 inhibitor, inhibited STAT3 phosphorylation and reversed the HCC phenotype of PRMT1 expression. Conclusions: We revealed a significant role for PRMT1 in HCC progression and metastasis in vitro and in vivo via STAT3 signalling pathway activation. PRMT1 may be a potential novel prognostic biomarker and new therapeutic target for HCC.